PENGARUH TARIF KAMAR TERHADAP KEPUASAN DAN MINAT PASIEN DALAM PEMBELIAN ULANG JASA RAWAT INAP DI RUMAH SAKIT PANTI RAPIH YOGYAKARTA - Soesanto, Harry (JURNAL BISNIS STRATEGI, 1998)
The National  development  being implemented in six PELITA bring a good result in health care  sector.  The hospital is getting  isolate  as  it own definite the tariff for services which have been given to consumer; because not all hospital stand alone to definite the services. As an effect, definite tariff is first tariff and the definite of consumer tendency to come with comfirmable tariff. This research has a tendency (1) to identify room  tariff influence,  and the relationship  between  patient  satisfaction and patient  willingness in rebuying in patient services  in  Panti Rapih hospital;  (2) to  identity consumer behaviour about patient satisfaction and to repurchase  for health  services  in Panti Rapih hospital.Research design   applied was on observational research (non experimental), and the research subject in patient.   Sample   was  drawn  as purpossive  with  definitelly criteria. Data were collect through from question which has been  fill by responden. And result will  be examination  as qualitative and quantitative with SPSS/PC + program. The result showed that (1) subject desire  to use Panti  Rapih hospital and the result has been  influence by satisfied servent depending with room  tariff; (2) research  subject show  that patient interest in rebuying in patient services, big enough to prediction behavior in decision  making.Based on  the  result,  it  was  concluded that patient interest in rebuying depending by patient satisfied, but a low cost of room  tariff has been  ignored.Thus a room  tariff is not the only  behavior reason to use Panti Rapih hospital, and not support by result of research calculation which mean that hypothesis has been denied.